2020
DOI: 10.1126/sciadv.abb9153
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of SARS-CoV-2 through recombination and strong purifying selection

Abstract: COVID-19 has become a global pandemic caused by the novel coronavirus SARS-CoV-2. Understanding the origins of SARS-CoV-2 is critical for deterring future zoonosis, discovering new drugs, and developing a vaccine. We show evidence of strong purifying selection around the receptor binding motif (RBM) in the spike and other genes among bat, pangolin, and human coronaviruses, suggesting similar evolutionary constraints in different host species. We also demonstrate that SARS-CoV-2’s entire RBM was introdu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
408
4
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(454 citation statements)
references
References 48 publications
(122 reference statements)
37
408
4
5
Order By: Relevance
“…2), suggesting that the evolution of these genes is not driven by recombination. Li et al studied the origin of SARS-CoV-2 and showed evidence of strong purifying selection in the S and other genes among bat, pangolin and human coronaviruses, indicating similarly strong evolutionary constraints in different host species [40]. Likewise, our results show that purifying selection drives evolution at the whole structural gene level of SARS-CoV-2 during its transmission between human hosts (Table 2; Additional le 1: Figure S1).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…2), suggesting that the evolution of these genes is not driven by recombination. Li et al studied the origin of SARS-CoV-2 and showed evidence of strong purifying selection in the S and other genes among bat, pangolin and human coronaviruses, indicating similarly strong evolutionary constraints in different host species [40]. Likewise, our results show that purifying selection drives evolution at the whole structural gene level of SARS-CoV-2 during its transmission between human hosts (Table 2; Additional le 1: Figure S1).…”
Section: Discussionsupporting
confidence: 73%
“…High nucleotide diversity (π; Table 1) of the S gene was detected in SARS-CoV-2 isolates, suggesting that it may bene t virus survival in human hosts. Recombination has played an important evolutionary role during the emergence of SARS-CoV-2 [39,40]. It has been reported that SARS-CoV-2 is a recombinant virus of bat and pangolin (Manis javanica) CoVs, suggesting a critical role of recombination [39].…”
Section: Discussionmentioning
confidence: 99%
“…Further work by others has generated a general picture of the structure of the SARS-CoV-2 genome based on breaks in homology in comparison to other known coronaviruses. As determined by Li et al (23), the vast majority of the RNA sequence of SARS-CoV-2 is derived from a relatively recent common ancestor with Bat_RaTG13. Similarity plots (SimPlot) detected a number of sudden changes in the percent similarity between SARS-CoV-2 and the base RaTG13-like sequence, accompanied by a change in similarity of RaTG13 to other viruses.…”
mentioning
confidence: 91%
“…For the purpose of my analysis, the direction of donation of the ACE2 receptor binding function is not relevant, simply that a clear area of recombination involving these otherwise closely related viruses from the same subclade has been identi ed by both Li et al (23) and Boni et al (25).…”
mentioning
confidence: 99%
“…The study further takes an unconventional approach to form an assumption that the hypothesis is true, and explores the possibility of future re-emergence (Li et al, 2020), taking into account COVID-19 infections occurring across geographical, multiethnic, multi-cultural environments, with the possible creation of multiple recombination platforms, and a large pool of SARS-CoV-2 quasispecies. Shen et al, while studying the genomic diversity of SARS-CoV-2 in the COVID-19 patients, have also emphasized on similar lines (Neher et al, 2020;Shen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%